Estudos sobre políticas energéticas e seus impactos na área da saúde: uma análise empírica causal - Rodrigues, Rômulo Eufrosino de Alencar (2023)
Although human capital is not directly observable, Benhabib and Spiegel (1994) reinforce that its quality and quantity are fundamental to the economy. Among the variables, health is considered an important proxy for this capital. The conception of health as one of the devices for human capital was first developed by Becker (2009) and later complemented by Grossman (1999), who states that it is a long-term stock that requires investment to grow, but which is depreciable. with time. Weak health can reduce work productivity, participation in the labor market and cause economic losses in the form of costs (CAI; KALB, 2006).